Gut feelings: Introducing the Everydayness of Eating as a Situated Pedagogical Attitude to Knowing and Caring for Naturecultures in Architecture Schools - Josymar Rodríguez Alfonzo; Liesbeth Huybrechts (Dearq)
This paper explores the incorporation in architectural education of everyday eating practices as a pedagogical approach. By involving architecture students in cooking, eating, and digesting together, the study seeks to move beyond conventional architectural training. Through a focus on eating, this approach aims to emphasize personal experiences as a primary source of knowledge. It employs autoethnography to reveal the transformative potential of centering the everydayness of eating in architectural learning. Findings highlight a profound link between eating-centered engagements and students' capacity to address complex societal and environmental issues, advocating for a shift towards embodied architectural education.